The Effect of Different Methods of Distribution and Methods Massed to The Passing Down Skills Volleyball of Game - Muhammad Syahrul Saleh; Syahruddin Syahruddin; M. Sahib Saleh (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The aims of this research are to determine the effect of the method of mass on the volleyball skills of passing, the effect of the distributed method on the volleyball skills of passing, and to know the difference between the methods of massed and distributed methods for passing the volleyball skills. This type of research is a thrue experiment with Randomized Group Pretest - Posttest Design. The independent variable is the method of massed and distributed methods while the dependent variable was passing the volleyball skills. The subjects were male students in grade 2 SMA Negeri 1 Gangking district Gantarang Bulukumba learning year 2011/2012, and as many as 30 people are purposive random sampling. The results showed that there was a significant effect of massed method for passing down skills in the game of volleyball (p <0.05), there was a significant effect of distributed method for passing down skills in the game of volleyball (p <0.05), and better-distributed method increases passing down the skills in the game of volleyball than massed method (p <0.05). Keyword: Massed, Distributed, Passing, Volleyball